Electron Capture from Molecular Hydrogen by Metastable Sn2+* Ions - Klaas Bijlsma; Lamberto Oltra; Emiel de Wit; Luc Assink; Ismanuel Rabadán; Luis Méndez; Ronnie Hoekstra (Atoms, 2024)
Over a wide and partly overlapping energy range, the single-electron capture cross-sections for collisions of metastable <semantics>Sn2+(5s5p <mmultiscripts>Po3</mmultiscripts>)</semantics> (<semantics>Sn2+∗</semantics>) ions with <semantics>H2</semantics> molecules were measured (0.1–10 keV) and calculated (0.3–1000 keV). The semi-classical calculations use a close-coupling method on a basis of electronic wavefunctions of the (SnH2)2+ system. The experimental cross-sections were extracted from double collisions in a crossed-beam experiment of <semantics>Sn3+</semantics> with <semantics>H2</semantics>. The measured capture cross-sections for <semantics>Sn2+∗</semantics> show good agreement with the calculations between 2 and 10 keV, but increase toward lower energies, whereas the calculations decrease. Additional Landau–Zener calculations were performed and show that the inclusion of spin-orbit splitting cannot explain the large cross-sections at the lowest energies which we now assume to be likely due to vibrational effects in the molecular hydrogen target.